2021
DOI: 10.1002/jdn.10113
|View full text |Cite
|
Sign up to set email alerts
|

The role of Vitamin B12 and genetic risk factors in the etiology of neural tube defects: A systematic review

Abstract: Neural tube defects (NTDs) are birth defects that arise during embryogenesis when normal neural tube closure fails to occur. According to the World Health Organization, NTDs are detected annually in approximately 300,000 neonates worldwide. The exact etiology of NTDs remains complex and poorly understood. It is generally agreed that most NTD cases are of multifactorial origin, having a combination of multiple genes and a number of environmental risk factors. The role of folic acid, vitamin B12 deficiency, gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…18 The anatomical position of myelomeningocele varies in literature however it has often present at 22.3% to 55.7% lumbosacral, cervical 1.8% to 5.6%, cervicothoracic 0.9%, thoracic 4.2%, lumbar 16.8% to 55.7%, sacral 16% to 34.5% and in 0.9% cervical, 5.6% thoracolumbar, and 16% sacral injuries were reported. [19][20] Age of pediatric patients was not statistically significant in our study which was found to be similar to the Lillegard J.B. et al, study results i.e., with two groups of OMFS (open maternal-fetal surgery) for fMMC (fetal myelomeningocele) closure compared with fetal and maternal outcomes (anterior and posterior placental locations) and found insignificance in gestational age at the time of delivery (p = 0.583). 21 In the Management of Myelomeningocele Study (MOMS) on 161 cohort patients, the children's average age at the time of the study visit was 7.8 years (range 5.9 -10.3).…”
Section: Discussionsupporting
confidence: 86%
“…18 The anatomical position of myelomeningocele varies in literature however it has often present at 22.3% to 55.7% lumbosacral, cervical 1.8% to 5.6%, cervicothoracic 0.9%, thoracic 4.2%, lumbar 16.8% to 55.7%, sacral 16% to 34.5% and in 0.9% cervical, 5.6% thoracolumbar, and 16% sacral injuries were reported. [19][20] Age of pediatric patients was not statistically significant in our study which was found to be similar to the Lillegard J.B. et al, study results i.e., with two groups of OMFS (open maternal-fetal surgery) for fMMC (fetal myelomeningocele) closure compared with fetal and maternal outcomes (anterior and posterior placental locations) and found insignificance in gestational age at the time of delivery (p = 0.583). 21 In the Management of Myelomeningocele Study (MOMS) on 161 cohort patients, the children's average age at the time of the study visit was 7.8 years (range 5.9 -10.3).…”
Section: Discussionsupporting
confidence: 86%
“…Genetics, maternal diminished folate status, maternal obesity, ambient air pollution, smoking, and maternal alcohol use are among the most important risk factor for NTDs 3,4,9,15,21,27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the early phase of pregnancy represents a period of high embryonic developmental vulnerability that is critically dependent on the adequate provision of interacting nutrients involved in one-carbon metabolism, as most clearly exemplified in the case of NTDs, a group of congenital malformations of the central nervous system that arise from a failure of neural tube closure during embryogenesis. Sensitivity of neural tube closure to one-carbon metabolism is signified by the lowering of NTD risk associated with higher maternal folate ( MRC Vitamin Study Research Group, 1991 ; Czeizel et al, 2011 ; De-Regil et al, 2015 ; Yadav et al, 2021 ), vitamin B 12 ( Ray et al, 2007 ; Gu et al, 2012 ; Molloy, 2018 ; Wahbeh and Manyama 2021 ; Yadav et al, 2021 ), vitamin B 6 ( Candito et al, 2008 ), choline ( Shaw et al, 2004 ; Shaw et al, 2009 ), betaine ( Shaw et al, 2004 ), and methionine ( Shaw et al, 1997 ; Shaw et al, 2004 ) status.…”
Section: Introductionmentioning
confidence: 99%